Spontaneous pneumococcal peritonitis diagnosed by qPCR. (2019) - Jarovsky, Daniel; Grodzicki Ambrus, Thais; Galvão Gurgel, Mariana; Jenné Mimica, Marcelo; Volpe Arnoni, Mariana; Almeida, Flávia Jacqueline; Palazzi Sáfadi, Marco Aurélio; Naaman Berezin, Eitan
Abstract: Spontaneous bacterial peritonitis is an uncommon manifestation of invasive pneumococcal disease and frequently occurs when an underlying hepatic disease is present. Bacterial identification through culture can be particularly challenging in patients with prior or concurrent antimicrobial use. DNA amplification detects very few copies of target DNA under ideal conditions in CSF or pleural effusion and, therefore, can be useful in selected infections. A culture-negative spontaneous pneumococcal peritonitis without preexisting peritoneal disease diagnosed by qPCR is herein described.